Prothrombin Complex Concentrate for Rapid Reversal of Warfarin Anticoagulation to Allow Neuraxial Blockade - Conor Skerritt; Stephen Mannion (Case Reports in Anesthesiology)
The development of Prothrombin Complex Concentrates (PCCs) has led to better outcomes in patients receiving emergency reversal of warfarin. However, most published data describes the use of PCCs in the setting of major bleeding or emergent major surgery, with little information on neuraxial blockade. We describe a case of rapid warfarin reversal using PCC and subsequent surgery under spinal anaesthesia in an 87-year-old lady, for whom general anaesthesia was deemed high risk. Her international normalised ratio (INR) on the morning of surgery was 1.8, precluding neuraxial blockade; however, it was felt that given, the need for imminent surgery, immediate reversal of the warfarin was indicated. We administered a single dose of 23 units/kg PCC and 5 mg vitamin K. Her INR 1 hour following PCC was 1.2, and spinal anesthetic was administered. The patient then underwent excision of melanoma deposits from her leg and groin dissection. There were no complications, the patient recovered satisfactorily, and there were no thrombotic or hemorrhagic events at 30 days postoperatively. This case study demonstrates a novel use of PCCs; in certain patients, PCCs may be safely used for immediate reversal of warfarin to allow for neuraxial blockade, safer anaesthesia, and better outcomes.